Experimental studies on the biological effects of extracorporeal shock wave therapy on tendon models. A review of the literature - Visco, Vincenzo (Muscles Ligaments Tendons J, 2014)
Encouraging results using extracorporeal shock wave therapy (ESWT) for treating chronic tendinopathies were recently obtained, although the specific mechanisms by which it induces therapeutic effects remain largely unknown. In order to provide possible explications of such clinical efficacy, several reports have investigated the effects of ESWT on animal models and different kind of cultured cells. Our contribute in establishing the potential outcome of ESWT on human primary cultured tenocytes, derived from healthy compared to ruptured tendons, have supported the growing evidence that shock waves may supply faster post-injury recovery. The purpose of this review was to summarize and evaluate the available basic scientific evidences for using ESWT in tendon pathologies, suggesting possible shock waves-induced mechanisms of tissue repair.